Applications for the social inclusion of people with disabilities and reduced mobility: A systematic literature review - Kunkel, Maria Elizete; Lima, Anderson da Silva; Fazan, Leonardo Henrique (Seven Editora, 2023)
Information and Communication Technology (ICT) can potentially enhance the independence of people with disabilities using mobile applications. Comparing the results of various applications in the literature can be challenging. This systematic literature review reveals the development of applications on mobility, spatial orientation, obstacle prevention, and access to urban information. The findings highlight the complexity involved in the development and the relevance of these tools in promoting the independence of users with disabilities, as well as collaborative efforts. Developing such applications is a complex task due to the heterogeneity of the end-users, requiring the identification of the necessary resources for each group. Innovations in modifying the urban environment allow everyone to enjoy life in the city. Conclusion: Social inclusion demands collaborative action from professionals from diverse fields, the general population, and the government in developing applications that meet the needs of all. DOI:https://doi.org/10.56238/sevened2023.004-015